Push It to the Limit: Identification of Novel Amino Acid Changes on the Acetolactate Synthase Enzyme of Rice That Putatively Confer High Level of Tolerance to Different Imidazolinones - Buffon, Giseli; Lamb, Thainá Inês; Lopes, Mara Cristina Barbosa; Sperotto, Raul Antonio; Timmers, Luís Fernando Saraiva Macedo (Frontiers in Bioengineering and Biotechnology, 2020)
Advancements in genetically modified herbicide tolerance technology opened a new way to manage weed populations in crop fields. Since then, many important genetically modified crops that are tolerant to various herbicides have been developed and commercialized. Herbicides primarily act by disrupting key enzymes involved in essential metabolic or physiological processes associated with growth and development of plants. Most of the herbicide tolerant plants have been developed by introducing point mutations (non-GM approach) in the target site of herbicide action, due to the advantage of easier registration/release for commercial cultivation as well as wider public acceptance. Imidazolinones are probably the most widely targeted ones for developing herbicide tolerant crops through non-GM approach. In rice, several mutant lines carrying specific amino acids changes in Acetolactate Synthase (ALS) are able to tolerate different Imidazolinones, including Gly628Glu, Ser627Asn and a double substitution Trp548Leu / Ser627Ile. The combination of these mutant lines provide a reliable method to eliminate weeds in the fields. However, the continuous overuse of a single herbicide in a growing season increases the potential risk of evolution of resistant weeds, which has become a major concern in agriculture worldwide. For this reason, the discovery of novel mutations in ALS (Os02g30630) that can generate rice plants more tolerant to Imidazolinones still is a hot topic in plant-herbicide interaction field. With that in mind, we performed molecular docking of Imidazolinones (imazapic, imazapyr, imazaquin, and imazethapyr) on the binding cavity of ALS, identifying specific amino acids residues that interact with the four herbicides. After, introducing point mutations in these specific positions (one at a time) using computational Alanine scanning mutagenesis approach and recalculating the herbicide-enzyme interaction affinity, we detected novel mutation sites on the structure of ALS that can inhibit the binding of Imidazolinones better than the already known mutations. This rational approach allows the researcher/farmer to choose the number of point mutations to be inserted in a rice cultivar, which will be dependent on the type of Imidazolinone used. In order to obtain a rice cultivar able to tolerate the four Imidazolinone tested concomitantly, we suggest the mutation of six amino acid residues.